PROMOTING SELF-REGULATED LEARNING USING YOUTUBE: A SYSTEMATIC REVIEW - Aljabari, Muhammad Saddam Husein; Dwiniasih, Dwiniasih; Luthfiyyah, Roghibatul (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2023)
This article delves into the role of YouTube in education, with a particular focus on its potential to enrich self-directed learning, especially in the realm of listening skills. A thorough examination of 30 scholarly journals was carried out to evaluate the endorsement of YouTube as a tool for enhancing self-directed learning. Data analysis encompassed the creation of a matrix to discern the impact, types, and purposes of YouTube in educational settings. The findings underscore YouTube as a highly valuable resource for fostering self-directed learning, owing to its adaptability and ease of access. Trends were identified across publication years, research methodologies, participant demographics, study objectives, and YouTube's role in promoting self-regulated learning. Nevertheless, this study also sheds light on the limitations in the application of YouTube in specific educational contexts, influenced by subject matter and varying educational levels. In summary, YouTube exhibits substantial promise in education, but its effectiveness hinges on thoughtful implementation strategies tailored to address the unique needs of both students and teachers.